The distribution of harmful algal bloom (HAB) species in the east and west coasts of Sabah, Malaysia - Mohammad Noor, Normawaty; Al-Azad, Sujjat (2011)
Harmful algal blooms (HABs) are serious problems around the world including Malaysia. The events have been linked to thousand of human illness and mortalities and loss to aquaculture industries. In Sabah, the problems have been reported for the last decade particularly in the west coast of Sabah. To update the presence and the distribution of HAB species, samples of phytoplankton were collected at several different sites of the west and east coasts of Sabah during 2010 and 2011. Besides, other factors such as nutrient concentration (nitrate and phosphate) and physical-chemical parameters, which support the occurrences of HAB species were also studied. At each site, two stations were chosen which are near the coastal area and 5 km away from the coastal area. Results showed that Pyrodinium bahamense var. compressum and Cochlodinium polykrikoides, the two important HAB species in Sabah were only found in the west coast of Sabah. Other potential HAB species were found both in the west and east coasts of Sabah. The highest cell density of these potential HAB species in the west and east coasts recorded were 2.4 x 105 cells/L and 5.9 x 103 cells/L, respectively. Nutrients including phosphates and nitrates were found to play an important role in supporting the HAB occurrence. Higher nutrients concentration was recorded at station near to the coastal area compared to station away from the coastal area. These indicate that both the west and east coasts of Sabah have the potential of having HAB problem in the future.